2010
DOI: 10.5142/jgr.2010.34.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Korean Red Ginseng Supplementation on Eradication Rate and Gastric Volatile Sulfur Compound Levels after Helicobacter pylori Eradication Therapy

Abstract: This clinical study was performed to evaluate whether supplementation of proton pump inhibitor (PPI)-based triple therapy with Korean red ginseng can enhance Helicobacter pylori (H. pylori) eradication and reduce levels of halitosis-associated volatile sulfur compounds (VSCs) in the stomach. Seventy-six patients were randomized into an eradication regimen-only group (n=45) or an eradication regimen plus 10 weeks of Korean red ginseng supplementation group (n=31). The eradication regimen consisted of PPI b.i.d.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Twenty-eight trials originated from Korea [28]–[55], and two trials were conducted in Thailand [26] and the United Kingdom [27]. Sixteen studies [28], [32]–[41], [44]–[47], [53] were published in Korean, and 14 trials [26], [27], [29]–[31], [42], [43], [48]–[52], [54], [55] were written in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight trials originated from Korea [28]–[55], and two trials were conducted in Thailand [26] and the United Kingdom [27]. Sixteen studies [28], [32]–[41], [44]–[47], [53] were published in Korean, and 14 trials [26], [27], [29]–[31], [42], [43], [48]–[52], [54], [55] were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…The key data from studies in healthy persons are summarised in Table 1 [26]–[34], and the data regarding other various conditions are summarised in Table 2 [35]–[55]. The included RCTs used ginseng powder either in raw (4 studies) [35], [38], [53], [55] or in capsules (22 studies) [26]–[29], [31], [32], [34], [36], [37], [39]–[41], [43]–[48], [50][52], [54] and extract preparation (2 studies) [33], [42], while two studies [30], [49] did not report the preparation type of ginseng. They addressed a wide range of conditions: generally healthy (i.e., studies in healthy individuals) [26]–[34], erectile dysfunction [35]–[40], gastric cancer [41], [43], colon cancer [42], gastrointestinal carcinoma [44], chronic gastritis [45], diabetes mellitus [46], [47], androgenic alopecia [48], coronary artery [49], dry mouth [50], glaucoma [51], obesity [52], metabolic syndrome [53], dyspepsia and indigestion [54] and Alzheimer’s disease [55].…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation of the stomach was induced with EtOH/HCl according to a published method (Lee et al, 2010b;Okabe et al, 1986). Fasted ICR mice were orally treated with Ac-EE (200 mg/kg) or ranitidine (40 mg/kg) twice per day for three days.…”
Section: Etoh/hcl-induced Gastritismentioning
confidence: 99%
“…Besides these synthetic products, a large body of evidence suggests that regular consumption of fruits and vegetables can prevent different forms of GI cancers (Table 1). 74-132 Because it is estimated that two thirds to three quarters of gastric cancer worldwide are associated with H. pylori infection,133 it seems that the eradication of H. pylori and the control of gastric inflammation induced by the pathogen are essential in the prevention of gastric cancer. Previous our studies have shown that Korea red ginseng could rescue H. pylori -induced cytotoxicity,76 suppress H. pylori -induced 5-lipoxygenase pathway,77 and attenuate gastric inflammation through augmented eradication rates of H. pylori in the clinical study 78.…”
Section: Reality Of Cancer Prevention According To Agentsmentioning
confidence: 99%